2011
DOI: 10.1007/s10291-011-0210-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Compass M-1 signals

Abstract: An analysis of observations from China's first medium earth orbit satellite Compass M-1 is presented, with main focus on the first orbit and clock solution for this satellite. The orbit is computed from laser ranging measurements. Based on this orbit solution, the apparent clock offset is estimated using measurements from two GNSS receivers, which allow Compass tracking. The analysis of the clock solutions reveals unexpectedly high dynamics in the pseudorange and carrier-phase observations. Furthermore, carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(76 citation statements)
references
References 7 publications
6
70
0
Order By: Relevance
“…Furthermore, it was also confirmed that the carrier to noise density ratio (C/N0) for BDS-IGSO and GEO satellites, which are characterised by a much higher altitude, is 3-4 dB-Hz lower than common BDS-MEO satellites [45,46]. Thus, the starting point of the investigations given in this section is the analysis of the carrier to noise density ratio for E14 and E18 satellites registered at different altitudes.…”
Section: Signal Powersupporting
confidence: 52%
“…Furthermore, it was also confirmed that the carrier to noise density ratio (C/N0) for BDS-IGSO and GEO satellites, which are characterised by a much higher altitude, is 3-4 dB-Hz lower than common BDS-MEO satellites [45,46]. Thus, the starting point of the investigations given in this section is the analysis of the carrier to noise density ratio for E14 and E18 satellites registered at different altitudes.…”
Section: Signal Powersupporting
confidence: 52%
“…(17) with the values given in Table 1, and using the maximum values of SNR, which are usually reached close to zenith. It is worth noting here that BeiDou signals have high carrier-to-noise density ratios, which exceed the values for the signals of other constellations such as GPS and Galileo on the corresponding frequency bands [8]. In our test, SNR of BeiDou signals reached a maximum of 56 dBHz.…”
Section: Characterization Of the Stochastic Properties Of The Signalsmentioning
confidence: 57%
“…(3-4), and thus will not a ect T LOM or w−statistic, instability of the clocks will show up due to disturbance in the observations and their predicted values computed through the dynamic model. The clock of satellite PRN C30, the rst-launched MEO satellite (known as M1), was reported earlier by [8] to experience some problems. This was con rmed by our data analysis.…”
Section: Monitoring and Analysis Of Data Validation Parametersmentioning
confidence: 99%
“…A method has been presented to design optimal parameter sets for all these three types of satellites (Fu and Wu 2011). The clock offset was estimated by processing the BDS M1 observations based on the orbit solution from laser ranging measurements (Hauschild et al 2012). Unexpectedly high dynamics in the clock results were found, which affect both the pseudo-range and carrier phase measurements.…”
Section: Introductionmentioning
confidence: 99%